Early revealing of neurogenic disorders of urination in patients with anorectal anomalies - Makedonsky I.O. (Medičnì Perspektivi)
148 patients with anorectal malformations (ARM) were examined. Using clinical, X-ray, ultrasound and urodynamical methods of detections, factors which can cause bladder dysfunction in anorectal malformations are revealed. It was noted that patients with high and low forms of this defect have significant percentage of neurogenec disorders of urination. Absence of anomalies of spinal column development does not exclude these children from the group of scheduled profound urologic investigation. We propose ultrasound measurement of bladder wall thickness and 4-hour monitoring of voiding, urodynamic examination as early diagnostic methods of neurogenic bladder dysfunctions. For timely revealing and treatment of neurogenic disorders of urination we recommend urologic inves¬tigation to all ARM patients. Improvement of diagnostic methods and development of algorithm of revealing mentioned pathologies against ARM with the aim to prevent com¬plications in the urinary system, being perspective in decreasing lethality and disability.